2021
DOI: 10.1051/matecconf/202134500012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recuperator on the efficiency of ORC and TFC with very dry working fluid

Abstract: Organic Rankine Cycles (ORC) and Trilateral Flash Cycles (TFC) are very similar power cycles; ideally, they have a reversible adiabatic (isentropic) compression, an isobaric heating, an isentropic expansion and an isobaric cooling. The main difference is that for ORC, the heating includes the full evaporation of the working fluid (prior expansion); therefore, the expansion starts in a saturated or dry vapour state, while for TFC, the heating terminates upon reaching the saturated liquid states. Therefore, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…F I G U R E 4 η th for organic Rankine cycle (ORC), partial evaporator-ORC, and trilateral flash cycle by using HFE7500 fluid at various T max 353-533 K Therefore, the results indicated that HFE7000 behaves as normal dry working (ORC η th greater than TFC, and there is no intersection between the efficiencies at a specific temperature). 67,68 While by using HFE7500, there is the intersection between the η th of ORC and TFC; thus, the results indicate that HFE7500 behaves as very dry working fluids (which has η th intersection at a specific temperature, and TFC η th will be greater than ORC at high heat source temperature), see Ahmed et al 67,69 Concerning HFE7100, there is the intersection between the η th curve for ORC and TFC at a temperature extremely close to its T cr ; therefore, it behaves as normal dry fluid at low heat source temperature and behaves as very dry working fluids at a specific temperature that is close to its T cr . The temperature of thermal efficiencies intersections was at T = 425.2 K while it has T cr = 534.2 K and T = 455.9 K while its T cr is 468.4 K for HFE7500, and HFE7100, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…F I G U R E 4 η th for organic Rankine cycle (ORC), partial evaporator-ORC, and trilateral flash cycle by using HFE7500 fluid at various T max 353-533 K Therefore, the results indicated that HFE7000 behaves as normal dry working (ORC η th greater than TFC, and there is no intersection between the efficiencies at a specific temperature). 67,68 While by using HFE7500, there is the intersection between the η th of ORC and TFC; thus, the results indicate that HFE7500 behaves as very dry working fluids (which has η th intersection at a specific temperature, and TFC η th will be greater than ORC at high heat source temperature), see Ahmed et al 67,69 Concerning HFE7100, there is the intersection between the η th curve for ORC and TFC at a temperature extremely close to its T cr ; therefore, it behaves as normal dry fluid at low heat source temperature and behaves as very dry working fluids at a specific temperature that is close to its T cr . The temperature of thermal efficiencies intersections was at T = 425.2 K while it has T cr = 534.2 K and T = 455.9 K while its T cr is 468.4 K for HFE7500, and HFE7100, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…By using HFE7000, the η th improvement for ORC overcome TFC. Therefore, these results indicated that HFE7000 behaves as normal dry working fluids (ORC η th greater than TFC, and there is no intersection between the efficiencies at a specific temperature) as other fluids (some of HC, CO 2 , and Water) which are studied in Ahmed et al 67,68 While HFE7500 behaves as very dry working fluids (which has η th intersection at a specific temperature and TFC η th greater than ORC), as dodecane, see Ahmed et al 67,69 HFE7100 behaves as normal dry working fluids at low T max and as very dry working fluids at a temperature close to its T cr . The thermal efficiencies intersections temperature was at T = 425.2 K while T cr = 534.2 K, and T = 455.9 K while its T cr is 468.4 K for HFE7500 and HFE7100, respectively.…”
Section: Thermal Efficiency Comparison Of Orcmentioning
confidence: 91%
“…[27][28][29] Heat recovery can increase cycle efficiency in mixed and pure working fluids. 30 Therefore some heat recovery devices (recuperator or regenerator [31][32][33] ) are recommended for all cycles that have recoverable heat, whether ORC or traditional RC, 34,35 which can be subcritical, transcritical, or supercritical cycles. 36,37 A previous study showed that, for the Rankine-like cycles (ORC, steam-RC, and subcritical CO 2 cycle), the thermal efficiency is generally higher than for TFC.…”
Section: Introductionmentioning
confidence: 99%